UNA RÉPLICA A “LA SOCIOLOGÍA CRÍTICA DE HENRI LEFEBVRE”, DE ROY ALFARO VARGAS - García, George I. (Universidad de Costa Rica, 2013)
This paper replies to the remarks in Roy Alfaro Vargas’s article “La sociología crítica de Henri Lefebvre” regarding George García’s book Las sombras de la modernidad.